Diderot's Letter on the Blind as Disability Political Theory. (February 2020) - Hirschmann, Nancy J.
This essay considers Denis Diderot's Letter on the Blind for the Use of Those Who Can See as a work that can contribute to a disability political theory. By recounting the experiences of visually impaired persons in their own words, Diderot opens up possibilities for a disability politics of self-representation, maintaining that sighted persons should listen to blind persons' accounts of their own experience rather than relying on their own imaginings and assumptions. By using blind experiences to challenge a philosophical problem that intrigued philosophers of the seventeenth and eighteenth centuries amid often-unsuccessful efforts to "cure" blindness through cataract surgeries, Diderot develops a powerful critique of the empiricist stress on vision as the primary source of perception and provides a remarkably forward-looking critique of disablist attitudes toward the blind. Through this philosophical discourse, he engages a political argument about the way knowledge is gathered, evaluated, and interpreted through relationships of power.